Biosensing Technologies for Mycobacterium tuberculosis Detection: Status and New Developments. (1st March 2011) - Zhou, Lixia; He, Xiaoxiao; He, Dinggeng; Wang, Kemin; Qin, Dilan
Abstract : Biosensing technologies promise to improve Mycobacterium tuberculosis ( M. tuberculosis ) detection and management in clinical diagnosis, food analysis, bioprocess, and environmental monitoring. A variety of portable, rapid, and sensitive biosensors with immediate "on-the-spot" interpretation have been developed for M. tuberculosis detection based on different biological elements recognition systems and basic signal transducer principles. Here, we present a synopsis of current developments of biosensing technologies for M. tuberculosis detection, which are classified on the basis of basic signal transducer principles, including piezoelectric quartz crystal biosensors, electrochemical biosensors, and magnetoelastic biosensors. Special attention is paid to the methods for improving the framework and analytical parameters of the biosensors, including sensitivity and analysis time as well as automation of analysis procedures. Challenges and perspectives of biosensing technologies development for M. tuberculosis detection are also discussed in the final part of this paper.